Association between frailty and caregiving needs: a cross-country comparison between the USA and China - Hoh, Roanne Minxuan (Nanyang Technological University, 2024)
This study examines the relationship between frailty and caregiving burden across two geographical settings in China and the USA. Datasets from China Health and Retirement Longitudinal Study (CHARLS) and Health and Retirement Study (HRS) were used to conduct OLS regression. Worsening frailty status is associated with an increase in hours and cost of care received. The mechanism driving the increase in care received primarily lies in informal care received. The increase in total hours of help received is driven by increases in unpaid help as well as help from family members. Through our findings, policymakers should consider that frailty primarily burdens familial caregivers, and that frailty has an economic cost beyond just healthcare costs.